Invasive Listeriosis of Intracardiac Device - Prerna Sharma; Mohamed Yassin (Case Reports in Medicine)
Introduction. Listeria monocytogenes is a food-borne pathogen which can cause invasive infection in immunocompromised adults. Listeria has been known to cause infections during pregnancy and in older adults. Listeria endocarditis is a rare condition. A case of listeria-related intracardiac device infection is reported below. Case Report. A 74-year-old male with a past medical history of coronary artery disease, congestive cardiac failure, permanent atrial fibrillation status after nodal ablation, and placement of a biventricular pacemaker presented to the hospital with complaints of generalized fatigue. He was found to have listeria bacteremia, and transthoracic echocardiogram (TTE) showed pacemaker lead vegetation. The patient was treated with 6 weeks of vancomycin followed by oral suppression with amoxicillin. Discussion. Listeria can affect native valves, prosthetic valves, or nonvalvular intracardiac devices. The mean age of prosthetic valve endocarditis has been reported to be 67 years with male-to-female ratio 1.7 : 1 and mitral-to-aortic valve ratio 1.3 : 1. There have been case reports of listeria prosthetic valve endocarditis; however, there is paucity of literature on listeria-related pacemaker lead infection. Treatment is mostly a combination of penicillin and aminoglycosides for 4–6 weeks. Surgical removal of the infected device is preferred. Invasive listeriosis is a rare but fatal entity which should be identified and treated promptly to ensure a good outcome.